COVID-19 in New Orleans: a nephrology clinical and education perspective and lessons learned (2020)
New Orleans’ first case of COVID-19 was reported on March 9, 2020 with a subsequent rapid rise in the number of cases throughout the state of Louisiana. Traditional educational efforts were no longer viable with social distancing and stay-athome orders, therefore virtual didactics were integrated into our curriculum. Due to an exponential increase in the number of patients with acute kidney injury requiring kidney replacement therapy, the nephrology sections at Louisiana State University School of Medicine and Tulane University School of Medicine adapted their clinical workflows to accommodate these increased clinical volumes by utilizing prolonged intermittent kidney replacement therapies and acute peritoneal dialysis as well as other strategies to mitigate nursing burnout and decrease scarce resource utilization. Telehealth was implemented in outpatient clinics and dialysis units to protect vulnerable patients with kidney disease while maintaining access to care. Lessons learned from this pandemic and subsequent response may be utilized for future responses in similar situations.